2017
DOI: 10.1007/s40618-017-0701-3
|View full text |Cite
|
Sign up to set email alerts
|

Persistence with denosumab therapy in women affected by osteoporosis with fragility fractures: a multicenter observational real practice study in Italy

Abstract: Persistence to denosumab treatment in our observational real practice study was very high. These results suggest that factors such as frequency of visits, pharmacological schedule, and opportunity to call the doctor might play an important role in the persistence and adherence to treatment to obtain maximum therapeutic effect and avoid further fragility fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…Previous persistence studies of denosumab covering the USA, Canada and several European countries excluding the UK have reported persistence at 12 months of 55.9-99.1% and at 24 months of 34.8-99.5% [24][25][26][27][28][29][30][31][32][33][34][35]. In contrast, for other parenteral therapies, the previous studies reported persistence at 12 months of 33.8-74.5%, and for oral therapies reported 10-78% [21,28].…”
Section: Discussionmentioning
confidence: 94%
“…Previous persistence studies of denosumab covering the USA, Canada and several European countries excluding the UK have reported persistence at 12 months of 55.9-99.1% and at 24 months of 34.8-99.5% [24][25][26][27][28][29][30][31][32][33][34][35]. In contrast, for other parenteral therapies, the previous studies reported persistence at 12 months of 33.8-74.5%, and for oral therapies reported 10-78% [21,28].…”
Section: Discussionmentioning
confidence: 94%
“…In fact, a large number of patients reporting a fragility fracture in the placebo and teriparatide groups sustained the traumatic event during the first few weeks of treatment 28,30 and the differences in fracture rates between the two treatment arms were minimal at 12 and 18 months. 9,30,31 Moreover, the observations of both enhanced anabolic effect and lower bone resorption with abaloparatide use compared to teriparatide therapy have also been questioned. 31…”
Section: New Anabolic Drugs: Abaloparatidementioning
confidence: 99%
“…7 Moreover, compliance and persistence to BP therapy are generally poor. 8 Denosumab is an advancement in antiresorptive therapy especially for enhancing adherence and persistence to treatment 9 as well as for a putative stimulation of osteoblastic activity in specific areas of cortical bone, 10 as evidenced by animal studies, but not yet confirmed in humans. 11 Furthermore, the suppression of bone turnover caused by antiresorptive drugs may explain osteonecrosis of the jaw and atypical femoral fractures which can be observed in patients with high-dose or long-term treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The receptor activator of nuclear factor-kB ligand (RANKL)/osteoprotegerin (OPG) system is one of the main regulators of bone remodeling (28). Denosumab, a RANKL pathway inhibitor monoclonal antibody, has been widely used in the treatment of osteoporosis (29)(30)(31)(32)(33). Increased osteoblast expression of RANKL has been previously observed in unloading conditions, such as SCI, resulting in an increased RANKL/OPG ratio (34)(35)(36)(37)(38).…”
Section: Denosumabmentioning
confidence: 99%